The biology of unconventional invasion of Duffy-negative reticulocytes by Plasmodium vivax and its implication in malaria epidemiology and public health - Lemu Golassa; Lucas Amenga-Etego; Eugenia Lo; Alfred Amambua-Ngwa (Malaria Journal, 2020)
Abstract Plasmodium vivax has been largely neglected over the past century, despite a widespread recognition of its burden across region where it is endemic. The parasite invades reticulocytes, employing the interaction between Plasmodium vivax Duffy binding protein (PvDBP) and human Duffy antigen receptor for chemokines (DARC). However, P. vivax has now been observed in Duffy-negative individuals, presenting a potentially serious public health problem as the majority of African populations are Duffy-negative. Invasion of Duffy-negative reticulocytes is suggested to be through duplication of the PvDBP and a novel protein encoded by P. vivax erythrocyte binding protein (EBP) genes. The emergence and spread of specific P. vivax strains with ability to invade Duffy-negative reticulocytes has, therefore, drawn substantial attention and further complicated the epidemiology and public health implication of vivax malaria. Given the right environment and vectorial capacity for transmission coupled with the parasite’s ability to invade Duffy-negative individuals, P. vivax could increase its epidemiological significance in Africa. In this review, authors present accruing knowledge on the paradigm shift in P. vivax invasion of Duffy-negative reticulocytes against the established mechanism of invading only Duffy-positive individuals and offer a perspective on the epidemiological diagnostic and public health implication in Africa.